Development of an Alqur'an Assisted Geography E-Book Using the Kvisoft Flipbook Maker Application on the Subject of Geography - Mukhtar, Mukhtar; Rahmi Novalita, Rahmi Novalita; Fitrah, Hariki (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This research aims to describe the validity and effectiveness of geography e-books assisted by the Al-Qur'an using the Kvisoft flipbook maker application in geography subjects. The type of research is Research & Development (R&D) using the ADDIE model. This research involved expert validators, namely material experts, language experts and teaching materials experts. The test subjects for the product development in this research were class X students at Putra Bangsa Lhoksukon State High School, North Aceh Regency. Data collection techniques use observation sheets, questionnaires and documentation. Data analysis techniques use percentage and mean analysis. The results of the research show that a) the validity of the geography e-book assisted by the Al-Qur'an using the kvisoft flip book maker application in geography subjects is classified as very valid in terms of the appropriateness of presentation (4.5), appropriateness of content (4.4), appropriateness of discussion (4.4), and graphical feasibility (4.2), b) There is an increase in student learning outcomes before and after using e-books. In the initial test, the score was 51 in the Poor category. Meanwhile, in the final test he obtained a score of 91 in the good category.